The Nuremberg War Crimes Trial and its Policy Consequences Today - Griech-Polelle, Beth A. (Nomos Verlagsgesellschaft mbH & Co. KG, 2020)
Justice Robert H. Jackson, plenipotentiary for planning the Allies trial at the International Military Tribunal, called the trial "one of the most significant tributes ever paid by power to reason." In Justice Jackson's opening statement he made it clear that the trial at Nuremberg was to mark a new beginning in human history; that Nuremberg would serve to establish principles that could serve as benchmarks for all human behavior. This revised and extended Edition seeks to address both the short-term effects of the International Military Tribunal and the current impact that the trials have had on international law. The first section of the book contains essays which are written by leading scholars such as Christoph J.M. Safferling, looking at German participation in the Nuremberg Trials, to Winifried R. Garscha's examination of Austrian War Crimes Trials and the concept of "Violation of Human Dignity." This section will also include an examination of the influence of Nuremberg on the Tokyo War Crimes Trial. The second section of the book addresses the present-day impact of Nuremberg on international law. This section contains essays on selective justice, human rights litigation, the creation of hybrid tribunals, with new essays addressing sexual and gender-based violence in conflict zones, as well as new work on the Nuremberg Project, located at Harvard University. The hope for this volume is that the spirit of Nuremberg will be revived. In the words of Henry T. King, Jr., who was a young lawyer serving at the IMT, stated in the preface, "A better and more peaceful world based on justice is within our grasp,(...), we have a golden opportunity to build a more secure future for generations to come." Richter Robert H. Jackson, Bevollmächtigter für die Planung des Prozesses der Alliierten vor dem Internationalen Militärtribunal, nannte den Prozess "one of the most significant tributes ever paid by power to reason". In seiner Eröffnungsrede machte Jackson deutlich, dass der Nürnberger Prozess einen Neuanfang in der Menschheitsgeschichte markieren sollte; dass Nürnberg dazu dienen würde, Prinzipien zu etablieren, die als Maßstab für alles menschliche Verhalten dienen könnten. Diese überarbeitete Neuauflage befasst sich sowohl mit den kurzfristigen Auswirkungen des Internationalen Militärgerichtshofs als auch mit den aktuellen Auswirkungen der Prozesse auf das Völkerrecht. Der erste Teil des Buches enthält Aufsätze von führenden Wissenschaftlern wie Christoph J.M. Safferling über die deutsche Beteiligung an den Nürnberger Prozessen, zu Winifried R. Garschas Untersuchung der österreichischen Kriegsverbrecherprozesse und das Konzept der "Verletzung der Menschenwürde". Außerdem wird der Einfluss Nürnbergs auf den Kriegsverbrecherprozess in Tokio untersucht. Der zweite Teil des Buches befasst sich mit den heutigen Auswirkungen Nürnbergs auf das Völkerrecht, mit Beiträgen über selektive Gerechtigkeit, Menschenrechtsstreitigkeiten, die Schaffung hybrider Tribunale. Neue Aufsätze beschäftigen sich mit sexueller und geschlechtsspezifischer Gewalt in Konfliktgebieten sowie mit dem Nürnberger Projekt an der Harvard University. Die Hoffnung für diesen Band ist, dass der Geist von Nürnberg wiederbelebt wird. In den Worten von Henry T. King, Jr., der als junger Anwalt am IMT tätig war, heißt es im Vorwort: "A better and more peaceful world based on justice is within our grasp (...), we have a golden opportunity to build a more secure future for generations to come."